Simultaneous Determination of Tamulosin Hydrochloride and Finasteride in Formulations by Reverse-Phase HPLC - GOWRI SANKAR, D.; DURVASA RAO, B.; SAI KISHORE, V.; MURTHY, T.E.G.K. (Asian Journal of Chemistry, 2010)
A simple, precise, rapid, reproducible and selective reverse phase HPLC method has been developed for the estimation of tamsulosin hydrochloride and finasteride in capsules. This method is based on using hypersil C 18, 5 μ column having 250 × 4.5 mm i.d., in isocratic mode with mobile phase of acetonitrile and water in the ratio of 60:40 v/v. The flow rate was 1 mL/min and efluents were monitored at 240 nm. The retention times of tamsulosin hydrochloride and finasteride were 3.92 and 5.45 min respectively and linearity ranges were in the range of 0.2-0.8 μg/mL and 2-10 μg/mL respectively.